Transcriptome Analysis Reveals Impaired Fertility and Immunity Under Salinity Exposure in Juvenile Grass Carp - Zhang, Jingjing; Wu, Zhi; He, Yujie; Li, Xinhui; Li, Jie (Frontiers in Marine Science, 2021)
Grass carp, Ctenopharyngodon idellus, is one of the most economically important aquaculture species and is widely cultured in China. However, its wild populations in many rivers decline increasingly and seawater intrusion is one of the most important threats to their survival. However, the mechanisms underlying the decline due to salinity pressure are still unknown. Here, we performed a comparative transcriptome analysis of C. idellus larval in response to salinity exposures and a total of 481 differentially expression genes (DEGs) were identified. These DEGs were significantly enriched in 8 KEGG pathways, among which steroid biosynthesis was the most important one with the highest rich score, the pathway plays an important role in the development of testes and ovary. Interestingly, all DEGs in steroid biosynthesis showed down regulation, indicating salinity exposure may pose a damage to fertility of C. idellus. Furthermore, three immunity-associated pathways (cytokine-cytokine receptor interaction, toll-like receptor signaling pathway and NOD-like receptor signaling pathway) were also significantly enriched, suggesting impaired immunity and high risk of disease infection under salinity exposure. Overall, the damage of both fertility and immunity would decrease the number of offspring and increase the risk of death due to disease infection. Our results provide a potential molecular mechanism underlying decline of wild C. idellus population in Pearl River.